ANALISIS PEMBIAYAAN KPR SYARIAH DI INDONESIA DAN MALAYSIA - Apriliansyah, Fikry; Kusnendi; Cakhyaneu, Aneu (Accounting Department, Politeknik Negeri Bandung, 2024)
Islamic mortgage is a customer financing product for purchasing homes. Islamic mortgage can be conducted using three contracts: murabahah, MMQ, and tawarruq. There was a phenomenon of declining growth in Shariah-compliant home financing in Indonesia and Malaysia in 2019 and 2020. This study aims to examine the influence of interest rates, Financing to Deposit Ratio (FDR), and bank size on Shariah-compliant home financing in Shariah Commercial Banks in Indonesia and Malaysia from 2016 to 2020. The subjects of this study are the Shariah Commercial Banks in Indonesia and Malaysia. The research methods used are descriptive and comparative. The population of the study consists of 30 Shariah Commercial Banks in Indonesia and Malaysia. Data collection methods are conducted through literature review and documentation. The sample size for this study is 13 banks. The statistical analysis technique used is panel data regression analysis and t-test. The dependent variable in this study is the total amount of Islamic mortgage, while the independent variables are interest rates, Financing to Deposit Ratio (FDR), and bank size. The results of the descriptive analysis show that Islamic mortgage in Indonesia and Malaysia from 2016 to 2020 tends to increase, interest rates tend to fluctuate, Financing to Deposit Ratio (FDR) tends to decrease, and bank size tends to increase. Furthermore, bank size has a positive effect on Shariah-compliant home financing. However, interest rates and Financing to Deposit Ratio (FDR) do not have an effect on Shariah-compliant home financing. Additionally, there is a significant difference in Islamic mortgage in Shariah Commercial Banks between Indonesia and Malaysia. The implication of this study is that bank size plays an important role in Shariah-compliant home financing in Indonesia and Malaysia.